Effect of different finishing and polishing techniques on the surface roughness of microfilled, hybrid and packable composite resins - Barbosa,Silvia Helena (2005)
This study examined the average surface roughness (Ra, µm) of 2 microfilled (Durafill and Perfection), 1 hybrid (Filtek Z250) and 2 packable composite resins (Surefil and Fill Magic), before (baseline) and after eight different finishing and polishing treatments. The surface roughness was assessed using a profilometer. Ten specimens of each composite resin were randomly subjected to one of the following finishing/polishing techniques: A - carbide burs; B - fine/extrafine diamond burs; C - Sof-Lex aluminum oxide discs; D - Super-Snap aluminum oxide discs; E - rubber polishing points + fine/extrafine polishing pastes; F - diamond burs + rubber polishing points + fine/extrafine polishing pastes; G - diamond burs + Sof-Lex system; H - diamond burs + Super-Snap system. Data were analyzed using two-way ANOVA and Tukey's HSD test. Significant differences (p<0.05) were detected among both the resins and the finishing/polishing techniques. For all resins, the use of diamond burs resulted in the greatest surface roughness (Ra: 0.69 to 1.44 µm). The lowest Ra means were obtained for the specimens treated with Sof-Lex discs (Ra: 0.11 to 0.25 µm). The Ra values of Durafill were lower than those of Perfection and Filtek Z250, and these in turn had lower Ra than the packable composite resins. Overall, the smoothest surfaces were obtained with the use the complete sequence of Sof-Lex discs. In areas that could not be reached by the aluminum oxide discs, the carbide burs and the association between rubber points and polishing pastes produced satisfactory surface smoothness for the packable and hybrid composite resins, respectively.